Antimalarial endoperoxides: synthesis and implications of the mode of action - Gialou, Irene; Varotsis, Constantinos; Koutsoupakis, Constantinos (My University, 2002)
Abstract 6,7-Dioxabicyclo[3.2.2]non-8-ene 2 and 1-isopropyl-4-methyl-2,3- dioxabicyclo[2.2.2]oct-5-ene (ascaridol) 3 were prepared as simplified, endoperoxide versions of clinically used antimalarial drugs. Fourier transform infrared (FTIR) technique in conjunction with 18O 2- enriched compound 2 has been applied in probing the bonds of the endoperoxide moiety and the bonds of the rings owing to the presence of the O-O, the C-O, the O-O-C as well as the C=O modes in the spectrum. The endoperoxide moiety is especially useful in this regard because the homolytic cleavage of the O-O bond can be characterized and hence can be used to assess the vibrational properties of the O- and C-centered radicals and subsequently that of the C-C bond cleavage. The cleavage of the O-O bond, and the ability to correlate vibrational properties of the reaction products with structural properties of the isolated products suggest that infrared spectroscopy is an appropriate tool to study the mode of action of antimalarial endoperoxides.
Keywords: Chemical bond; Fragmentation reactions; Infrared spectroscopy